Plasma levels of leptin in patients with pathological gambling, internet gaming disorder and alcohol use disorder. (October 2018) - Geisel, Olga; Hellweg, Rainer; Wiedemann, Klaus; Müller, Christian A.
Highlights: Leptin is not altered in abstinent patients with alcohol use disorder. Leptin correlates with copeptin in patients with pathological gambling. Leptin does not correlate with craving in alcohol use disorder. Leptin is not altered in patients with active Internet Gaming disorder. Abstract: Leptin has been suggested to be involved in the pathophysiology of addictive disorders via modulation of mesolimbic reward pathways. Previous studies in patients with substance use disorders (alcohol, tobacco, cocaine) found positive correlations of leptin blood levels with craving. Here, we investigated leptin blood levels in patients with non-substance related addictive disorders such as pathological gambling (PG) and internet gaming disorder (IGD) in comparison to patients with alcohol use disorder (AUD) and healthy controls. Plasma levels of leptin were measured in male patients with PG (n = 14), male patients with IGD (n = 11), male patients with AUD (n = 39) and male healthy controls (n = 12). Additionally, correlation analyses with blood levels of HPA axis hormones were performed. Leptin plasma levels of patients with PG, IGD or AUD and healthy controls did not differ significantly across groups. In patients with PG, leptin plasma levels were correlated with copeptin, a surrogate for arginine vasopressin. Our findings do not suggest an involvement of leptin in abstinent patients with AUD or in patients with active IGD. In patients with active PG, leptin blood levels were not related to craving for gambling, but leptin might be involved in PG via an interaction with the HPA axis.